Pemberdayaan UMKM Melalui Legalitas Usaha Pembuatan NIB dan Sertifikasi Halal di Desa Sidomukti Kepohbaru Bojonegoro - Oktivami, Endang; Ratnawati, Dewi; Hidayah, Cindy Rohmatul; Yana, Siti Feri Yana; Kurnia, Shelvia Dwi Kurnia; Saputri, Sinta Elisa Laras Saputri; Fitra, Lily Sulis; Rahmawati, Rizka Zulfita Auliya; Dewi, Sentiya Rahma Dewi; Mardhiyah, Siti Fadhilatum; Rokhmah, Siti Kurniatur; Febriana, Fauziah Yogi; Hanifah, Hafidhotul; Farida, Dina (Community: Jurnal Pengabdian Kepada Masyarakat, 2024)
Sidomukti Village is one of the villages in Kepohbaru District, Bojonegoro Regency, which has many Micro, Small and Medium Enterprises (MSMEs). In their development, MSMEs are still experiencing licensing problems such as the absence of Business Identification Numbers (NIB) and Halal Certificates for KKN Group 07 Students of the Attanwir Institute, in this case collaborating with Sidomukt Village: and the Bojonegoro Ministry of Religion Halal Product Instructor to provide assistance in making NIB and Halal Certification through the Online Single Submission (OSS) system. This asset assistance is carried out using the ABCD (Asset Based Community Development) approach with several stages including Inculturation Discovery, Dream, Define, Design, and Destiny. The steps taken to develop existing potential in the village community, namely observation, interviews, data collection on MSMEs, socialization and mentoring of MSMEs, evaluation and community creation. The results and assistance of this are that some MSME actors in Sidomukti village have NIB and halal certification. This assistance shows that socialization and assistance in making business legality can be the right solution to advance MSMEs in Sidomuktı village